McDonaldization and technology: the control and rationalization of contemporary lifestyles - Gadonski, Jaderson; Gois, Pedro Henrique de; Bobsin, Debora; Rosa, Ana Claudia da; Fonseca, Ketlen Pinto da Silva (Revista de Administração da UFSM, 2026)
Purpose: This study investigates the relationship between McDonaldization and technology, analyzing how the extreme rationalization of social processes, driven by Information Technologies, shapes contemporary lifestyles, organizations, and social interactions. The central objective is to understand whether digital McDonaldization structurally transforms human interactions and institutional functioning by reinforcing efficiency, predictability, control, and calculability. Design/methodology/approach: This qualitative, exploratory, and descriptive research is based on discourse analysis from five interviewees working in different economic sectors. Semi-structured interviews were conducted, and their narratives were analyzed according to the principles of McDonaldization proposed by Ritzer (2021). Discourse analysis followed Foucault’s (2014) approach, exploring internal and external discursive procedures that legitimize or challenge digital rationalization. Findings: Digital McDonaldization structures work and consumption, promoting efficiency and convenience but also reducing individual autonomy and imposing invisible control mechanisms mediated by algorithms and predictive systems. Research limitations/implications: The study includes a limited number of interviewees, restricting the generalization of results. Future research may adopt mixed methods to expand the analysis. Practical implications: The findings highlight the need to balance efficiency and flexibility in organizational models to prevent the dehumanization of labor and consumption relations. Social implications: The study reveals how digital rationalization affects subjectivity and reinforces algorithmic control over individual choices. Originality/value: This study contributes to the debate on McDonaldization and technology by expanding the understanding of digital rationalization and its effects on contemporary society.